Hulk teach. 1 - Brown, Jeffrey, 1975- (Graphix, an imprint of Scholastic, 2025)
"Bruce Banner, AKA the Hulk, is a genius scientist and super hero whose rage-outs have led him to damage way too much public property. After his latest meltdown, Tony Stark arranges a PR move to smooth things over. Hulk will perform community service--by teaching. Can Banner make it through the school year without destroying everything? And can middle school kids really learn anything when the Hulk is their teacher?"--